Casein Kinase 1 Underlies Temperature Compensation of Circadian Rhythms in Human Red Blood Cells. Issue 2 (April 2019) - Beale, Andrew D.; Kruchek, Emily; Kitcatt, Stephen J.; Henslee, Erin A.; Parry, Jack S.W.; Braun, Gabriella; Jabr, Rita; von Schantz, Malcolm; O'Neill, John S.; Labeed, Fatima H.
Temperature compensation and period determination by casein kinase 1 (CK1) are conserved features of eukaryotic circadian rhythms, whereas the clock gene transcription factors that facilitate daily gene expression rhythms differ between phylogenetic kingdoms. Human red blood cells (RBCs) exhibit temperature-compensated circadian rhythms, which, because RBCs lack nuclei, must occur in the absence of a circadian transcription-translation feedback loop. We tested whether period determination and temperature compensation are dependent on CKs in RBCs. As with nucleated cell types, broad-spectrum kinase inhibition with staurosporine lengthened the period of the RBC clock at 37°C, with more specific inhibition of CK1 and CK2 also eliciting robust changes in circadian period. Strikingly, inhibition of CK1 abolished temperature compensation and increased the Q10 for the period of oscillation in RBCs, similar to observations in nucleated cells. This indicates that CK1 activity is essential for circadian rhythms irrespective of the presence or absence of clock gene expression cycles.